Colorectal cancer chemoprevention: is aspirin still in the game?. Issue 1 (31st December 2022) - Grancher, Adrien; Michel, Pierre; Di Fiore, Frederic; Sefrioui, David
ABSTRACT: Screening strategies have demonstrated their potential for decreasing the incidence and mortality of cancers, particularly that of colorectal cancer (CRC). Another strategy that has been developed to reduce CRC occurrence is the use of chemoprevention agents. Among them, aspirin is the most promising. Aspirin acts in colorectal tumourigenesis through several mechanisms, either directly in tumor cells or in their microenvironment, such as through its anti-inflammatory activity or its effect on the modulation of platelet function. Many retrospective studies, as well as follow-up of large cohorts from trials with primary cardiovascular end points, have shown that long-term treatment with daily low-dose aspirin decreases the incidence of adenomas and colorectal cancers. Therefore, aspirin is currently recommended by the United States Preventive Services Task Force (USPSTF) for primary prevention of CRC in all patients aged 50 to 59 with a 10-y risk of cardiovascular events greater than 10%. Furthermore, several studies have also reported that long-term aspirin treatment taking after CRC resection decreases recurrence risk and increases overall survival, especially in patients with PIK3CA -mutated tumors. This review summarizes current knowledge on the pathophysiological mechanisms of aspirin chemoprevention, discusses the primary clinical results on CRC prevention and highlights the potential biomarkers identified to predict aspirin efficacy.